2020
DOI: 10.7554/elife.58723
|View full text |Cite
|
Sign up to set email alerts
|

Social dominance mediates behavioral adaptation to chronic stress in a sex-specific manner

Abstract: Sex differences and social context independently contribute to the development of stress-related disorders. However, less is known about how their interplay might influence behavior and physiology. Here we focused on social hierarchy status, a major component of the social environment in mice, and whether it influences the behavioral adaptation to chronic stress in a sex-specific manner. We used a high-throughput automated behavioral monitoring system to assess social dominance in same-sex group-living mice. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 54 publications
1
50
0
Order By: Relevance
“…Dominant animals, which have a smaller stress response to the variable stress, remain in a dominant position, whereas animals with larger stress responses drop to the bottom of the social hierarchy. This effect may take time as a single acute stressor did not alter hierarchy when measuring agonistic behavior in a social box (Karamihalev et al, 2020). Moreover, this prior work showed sex-specific behavioral effects in response to CVS.…”
Section: Discussionmentioning
confidence: 99%
“…Dominant animals, which have a smaller stress response to the variable stress, remain in a dominant position, whereas animals with larger stress responses drop to the bottom of the social hierarchy. This effect may take time as a single acute stressor did not alter hierarchy when measuring agonistic behavior in a social box (Karamihalev et al, 2020). Moreover, this prior work showed sex-specific behavioral effects in response to CVS.…”
Section: Discussionmentioning
confidence: 99%
“…The social environment has a powerful influence on how individuals experience and cope with negative encounters. Regardless of whether this negative encounter was an adverse environmental condition or an exposure to drugs of abuse, social behavior and social rank in particular, are important contributors to individual differences [ 100 ] and to the individual responses to environmental challenges [ 101 ]. However, for most of the studies, social behavior and rank have been identified on the basis of a detailed observation of pairs.…”
Section: Discussionmentioning
confidence: 99%
“…If larger numbers of mice per cage are used it is advisable to choose animals with similar bodyweight to minimize dominance and fighting, especially with male mice. We advise that when deciding on the number of mice to be placed into one cage the user should take into the consideration on pre-testing the animal’s social dominancy, especially when compared the phenotype between male and female ( van Den Berg et al., 2015 ; Williamson et al., 2019 ; Karamihalev et al., 2020 ) At the pre-monitoring week ( Figure 1 ), measure body composition, glucose tolerance, and basal metabolic profiles following the subsequent steps. Note: Sophisticated monitoring systems might not be accessible for all laboratories.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
“…If larger numbers of mice per cage are used it is advisable to choose animals with similar bodyweight to minimize dominance and fighting, especially with male mice. We advise that when deciding on the number of mice to be placed into one cage the user should take into the consideration on pre-testing the animal’s social dominancy, especially when compared the phenotype between male and female ( van Den Berg et al., 2015 ; Williamson et al., 2019 ; Karamihalev et al., 2020 )…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%